Ripensare l’11 Settembre con Derrida: Tra evento e autoimmunità (Altre Modernità, 2011)
In a way, after the September 11th terrorist attack, we have all had the feeling that we witnessed a real major event. However, the notion of event itself is semantically problematic. The 10th anniversary of this date offers us the opportunity to interrogate ourselves with a new question: was this indeed an event? To what extent? This is the very question which opens Jacques Derrida’s interview, undertaken by Giovanna Borradori in New York a few days after the attack. Indeed the French philosopher Derrida provides us with deep insights into the notion of event, its underpinnings and semantic roots. To a certain extent September 11th seems to be an event; indeed, how otherwise could it have given such a strong impression of being so? On the other hand however, it seems not to have been an event, in that it does not correspond to the Derridian definition of “event” as a surprise, as something totally unpredictable. September 11th - Derrida claims- was predictable and it’s not by chance that the US had created institutions such as the CIA or the NSA to defend themselves from this kind of threat. Nevertheless in understanding September 11th as something other than an event, we are forced to struggle with the question why was it that we first had the impression it was an event and why did it have such a strong impact on us?We are therefore confronted with two new important questions. The first leads us to reflect on the role that the media played with respect to September 11th. What would September 11th have been –Derrida asks himself- without TV? The second question concerns the auto-immune nature of this event, which explains its traumatic effect and stands as an emblem of that auto-immunity, which is the fundamental characteristic of present times, in this era of globalisation.